P2X4-receptor participates in EAAT3 regulation via BDNF-TrkB signaling in a model of trigeminal allodynia. Issue 1 (August 2018) - Liu, Chaoyang; Zhang, Yixin; Liu, Qing; Jiang, Li; Li, Maolin; Wang, Sha; Long, Ting; He, Wei; Kong, Xueying; Qin, Guangcheng; Chen, Lixue; Zhang, Yuhong; et al.
Objective: Previous studies of neuropathic pain have suggested that the P2X4 purinoceptor (P2X4R) in spinal microglia is essential for maintaining allodynia following nerve injury. However, little is known about its role in inflammatory soup-induced trigeminal allodynia, which closely mimics chronic migraine status. Here, we determined the contributions of P2X4R and related signaling pathways in an inflammatory soup-induced trigeminal allodynia model. Methods: P2X4R gene and protein levels in the trigeminal nucleus caudalis were analyzed following repeated dural inflammatory soup infusions. p38, brain-derived neurotrophic factor, excitatory amino acid transporter 3, c-Fos, and calcitonin gene-related peptide protein levels in the trigeminal nucleus caudalis, as well as trigeminal sensitivity, were assessed among the different groups. Immunofluorescence staining was used to detect protein localization and expression in the trigeminal nucleus caudalis. Results: Repeated inflammatory dural stimulation induced trigeminal hyperalgesia and the upregulation of P2X4R. Immunofluorescence revealed that P2X4R was expressed in trigeminal nucleus caudalis microglial cells. Blockage of P2X4R produced an anti-nociceptive effect, which was associated with an inhibition of inflammatory soup-induced increases in p38, brain-derived neurotrophic factor, excitatory amino acid transporter 3, c-Fos, and calcitonin gene-related peptide protein levels. The tyrosine receptor kinase B antagonist ANA-12 reversed trigeminal allodynia and the upregulation of excitatory amino acid transporter 3, c-Fos, and calcitonin gene-related peptide, whereas the agonist 7, 8-dihydroxyflavone exacerbated these effects. Double immunostaining indicated that p38 and brain-derived neurotrophic factor were mainly expressed in microglial cells, whereas excitatory amino acid transporter 3 was primarily expressed in trigeminal nucleus caudalis neurons. Conclusions: These data indicate that microglial P2X4R is involved in the regulation of excitatory amino acid transporter 3 via brain-derived neurotrophic factor-tyrosine receptor kinase B signaling following repeated inflammatory dural stimulation. Microglial P2X4R activation and microglia–neuron interactions in the trigeminal nucleus caudalis may play a role in the pathogenesis of migraine chronicity, and the modulation of P2X4R activation might be a potential therapeutic strategy.